Jane Austen and Critical Theory - Kramp, Michael (Taylor & Francis, 2021)
Jane Austen and Critical Theory is a collection of new essays that addresses the absence of Critical Theory in Austen studies-an absence that has limited the reach of Austen criticism. The collection brings together innovative scholars who ask new and challenging questions about the efficacy of Austen's work. This volume confronts mythical understandings of Austen as "Dear Aunt Jane," the early twentieth-century legacy of Austen as a cultural salve, and the persistent habit of reading her works for advice or instructions. The authors pursue a diversity of methods, encourage us to build new kinds of relationships to Austen and her writings, and demonstrate how these relationships might generate new ideas and possibilities-ideas and possibilities that promise to expand the ways in which we deploy Austen. The book specifically reminds us of the vital importance of Austen and her fiction for central concerns of the humanities, including the place of the individual within civil society, the potential for new identities and communities, the urgency to address racial and sexual oppression, and the need to imagine more just futures.